COACH THE PERSON, NOT THE PROBLEM;A GUIDE TO USING REFLECTIVE INQUIRY - MARCIA REYNOLDS (BERRETT-KOEHLER, 2020)
"From a founding member of the coaching movement comes a detailed guide to mastering one of a coach's toughest skills: thoughtfully reflecting clients' words and expressions back to them so they see themselves and their world through new eyes"--